Uso de ferramenta de captura eletrônica de dados para avaliação e orientação de higiene bucal em gestantes - Bortolo, Gabriela Petri de (2021)
Pregnancy is a transitory physiological condition that leads to different physical, biological and hormonal changes in women’s body. These changes - which are associated with inadequate eating habits and with negligence in oral hygiene - may increase the risk of oral diseases and affect the quality of life of both the pregnant women and their babies. Thus, educational activities emphasizing the importance of dental prenatal care are an excellent alternative for oral health promotion among pregnant women. Nowadays, information technology is an efficient tool used in this health promotion process. The aim of the current study is to assess oral hygiene practices and their impact on the quality of life of pregnant women, based on an oralcare guidance system. Cross-sectional study was carried out with 201 pregnant women living in Espírito Santo State, Brazil, who participated in specific WhatsApp groups for pregnant women. Their participation in the survey was consolidated when the electronic questionnaire was fully filled in. Adolescent pregnant women and those living in another state or country were not included in the data analysis carried out in the current study, although they also received feedback on their answers to the questionnaire. Data collection took place online, from August to November 2020, based on electronic Web-survey questionnaire developed on the Research Electronic Data Capture (REDCap) platform. The questionnaire comprised objective and discursive questions focused on pregnant women’s personal, socioeconomic and hygiene data, as well as on their self-perception about oral health, based on the application of the Oral Health Index Profile-14 (OHIP-14) scale. After the researcher had fully evaluated the questionnaire, pregnant women received a letter by e-mail about their current oral hygiene status and the likely impacts associated with the Praise-Instruct-Recommend (PIR) classification scores on their quality of life. Most pregnant women presented high sociodemographic conditions. With respect to oral hygiene practices, 53.7% of pregnant women received praise, whereas 46.3% needed instructions. Among them, 10% presented impact of oral health on quality of life; such an impact was associated with the fact that the affected women were the head of their families (OR= 4.26; 95%CI: 1.62-11.20). Oral health promotion strategies for pregnant women must be developed and applied as public health measure. Using intelligent technologies to promote oral health among pregnant women in pandemic times can be an important strategy to track and raise these women’s awareness about the importance of dental prenatal care. Thus, the PIR classification method can be used to promote health education and to screen pregnant women in need of oral healthcare. WhatsApp is effective as digital media resource used to propagate scientific research, whereas the REDCap platform is an effective tool to help developing smart technologies focused on research conducted in the oral health field, since it enables managing collected data in a satisfactory way.